Life Domains, Constraints, Motivations, and Intimate Partner Violence: Assessing the Generality of Agnew’s General Theory of Crime and Delinquency - Ngo, Fawn T. (Crime & delinquency, 2024)
Given the victim-offender overlap, it has been suggested that every theory about offenders implies a corresponding theory of victimization. We assess the above assertion concerning Agnew?s general theory of crime and delinquency within the context of intimate partner violence (IPV). Drawing data from the International Dating Violence Study, we examine the direct and indirect effects of the self, family, school/work, and peer domains on IPV perpetration and victimization. We found the four life domains significantly predicted both IPV perpetration and victimization and their effects on both outcome variables were mediated by the constraint and motivation factors. Our results indicate that the mechanisms that account for offending posited in Agnew?s perspective appear to be equally relevant and applicable for understanding victimization.